Methane biohydroxylation into methanol by Methylosinus trichosporium OB3b: possible limitations and formate use during reaction - Baldo, Héloïse; Ruiz-Valencia, Azariel; Cornette de Saint Cyr, Louis; Ramadier, Guillaume; Petit, Eddy; Belleville, Marie-Pierre; Sanchez-Marcano, José; Soussan, Laurence (Frontiers in Bioengineering and Biotechnology, 2024)
Methane (CH 4 ) hydroxylation into methanol (MeOH) by methanotrophic bacteria is an attractive and sustainable way to produce MeOH. The model strain Methylosinus trichosporium OB3b has been reported as an efficient hydroxylating biocatalyst. Nevertheless, previous works have shown that regardless of bioreactor design or operation mode, MeOH concentration reaches a threshold after a few hours, yet none of them investigated the reasons behind this. The present work monitored both MeOH and formate concentrations during CH 4 hydroxylation. Neither gaseous substrate nor nutrient shortage was evidenced. In the assayed reaction conditions, bacteria stress was shown to occur but methanol was not responsible for this. Formate addition was necessary to start MeOH production. NMR analyses with 13 C-formate proved that formate was dedicated to regenerate NADH. Formate was exhausted during reaction, but increased formate quantities were unable to prevent MeOH production stop. Formate mass balance showed that formate-to-methanol yield was around 50%, suggesting cell regulation phenomena. This work opens ways to possible physiological causes which will be further investigated. Finally, this study showed for the first time to our knowledge that the reaction can be operated in the native bacterial culture (i.e. the culture medium used for the bacterial culture in which MDH inhibitors were added), avoiding centrifugation steps and limiting hands-on time and water consumption.